CATCH DIFFERENCES OF BOTTOM LONG LINE USING FRESH AND SALTED FISH BAITS - Mahiswara Mahiswara; Wudianto Wudianto (Indonesian Journal of Agricultural Science, 2001)
Bottom long line is an important gear for catching demersal fish and normally uses fresh fish as bait. Recent development indicates that the fishing  grounds for bottom long line are  further away from the coast and consequently bait with longer life-time may be needed. Research on the use of fresh and salted fish baits for bottom long line has been conducted in the eastern Bali waters. In this study, salted and fresh baits were used simultaneously for fishing. The results showed that the catch of bottom long line using fresh bait was significantly higher than that for salted bait  indicating that other suitable preservation techniques are necessary.